PERCEIVED SUSCEPTIBILITY TO CHRONIC DISEASE AMONG HEALTHY PEOPLE QUESTIONNAIRE: DEVELOPMENT, VALIDITY AND RELIABILITY AMONG YOUNG IRAQI ADULTS - Harith Alaa; Shamsul Azhar Shah (Malaysian Journal of Public Health Medicine, 2018)
Chronic non-communicable diseases are the new emerging epidemic, and they are thought to challenge only rich countries; cardiovascular disease, cancer, diabetes, and other non-communicable diseases (NCDs) are now the leading cause of death and disability in low-income and middle-income countries, where they killed almost 8 million people younger than 60 years in 2013. Therefore, there is a need to develop a valid and reliable tool to measure the beliefs that influence people’s general behaviour, and a used to measure beliefs about chronic disease perceived susceptibility. The purpose of this study was to develop and validate the use of perception questionnaire among the young Iraqi adults. A total of 200 young adults participated who are free from any chronic diseases under study, and are living in Baghdad. The questionnaire, validated by an expert’s panel, translated to Arabic language, and pretested. Analyses included descriptive statistics of all the study variables, reliability estimates, and construct validity using confirmatory factor analysis (CFA). Results showed that mean age of respondents was 30 years old, majority were males 71.5%, and EFA showed that factor loading was more than 0.4. CFA results show that Chi-square (df) = 1.213(2); p value (>0.05) = 0.297. Internal consistency reliability analysis on health-related behaviour; special practice, information seeking and perceived probability of diseases have good Cronbach’s ? value of between 0.8 - 0.9. These findings revealed that validation is favourable and can be utilized on larger scale of sample to proceed with main study on chronic disease perceived susceptibility among healthy people.